Dhattura Lavana: An Eccentric Salt Preparation in Folklore - Amrutha, O.P.; Govinda, Sharma K.; Ajith, Kumar G.; Savitha, H.P. (Journal of Drug Delivery and Therapeutics, 2019)
Lavana kalpana is a formulation in Ayurveda which is prepared from combination of certain drugs with lavana (Salt). A particular heating pattern is followed for drugs and lavana in an earthen crucible by subjecting it to putapaka. Number of lavana kalpana like Narikela lavana Arka lavana and other such formulations are being practiced in Ayurveda. Dhattura lavana is also a formulation of Dhattura and lavana used in alcohol dependence. An attempt was made in this work to gather the information about this formulation. It is observed that this formulation is used by traditional practioners of Kerala. The reference of Dhattura lavana could not be found in the books or literatures of Ayurveda. Deviating from the general method of preparation of putapaka, Dhattura lavana is prepared in a unique way. In this formulation, a decoction of Dhattura is prepared first and to that equal amount of lavana is added and dehydrated. Keywords: Dhattura lavana, Lavana kalpana, madatyaya, tadarthakari chikitsa.